2013
DOI: 10.1084/jem.20122465
|View full text |Cite
|
Sign up to set email alerts
|

A role for gut-associated lymphoid tissue in shaping the human B cell repertoire

Abstract: Transitional 2 B cells home to gut-associated lymphoid tissue and present an activated phenotype in healthy subjects, but gut immune compartments are depleted in SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 33 publications
6
87
0
Order By: Relevance
“…It was also recently proposed that immature transitional 2 B cells are selectively recruited to the GALT for maturation into mature naive cells in healthy adults (39). However, we recently showed that an early gut flora including Escherichia coli and bifidobacteria was associated with higher numbers of CD27 + memory B cells later in childhood, but no relationship was found between the levels of CD5 + B cells and bacterial colonization (15).…”
Section: Discussionmentioning
confidence: 73%
“…It was also recently proposed that immature transitional 2 B cells are selectively recruited to the GALT for maturation into mature naive cells in healthy adults (39). However, we recently showed that an early gut flora including Escherichia coli and bifidobacteria was associated with higher numbers of CD27 + memory B cells later in childhood, but no relationship was found between the levels of CD5 + B cells and bacterial colonization (15).…”
Section: Discussionmentioning
confidence: 73%
“…(d) Mature naive B cells that are activated in the gut may home into the marginal zone of the spleen, contributing IgA antibodies that are specific for gut pathogens/commensal antigens to the serum IgA pool. Gut-resident B cells further contribute to the serum IgA pool in the form dimeric IgA (Vossenkamper et al, 2013;Mestecky et al, 1999). Figure is not drawn to scale.…”
Section: Sugar Residues In Serum Iga: Impact On Its Interactions and mentioning
confidence: 99%
“…Recent evidence suggests that naive B cells activated in the gut-associated lymphoid tissue may home in to the marginal zone of the spleen (Vossenkamper et al, 2013). Therefore IgA, specific for commensal or pathogenic bacteria, produced by plasma cells in the marginal zone may be secreted into the bloodstream.…”
Section: Serum Iga Function May Be Further Influenced By the Mucosal mentioning
confidence: 99%
“…Preferential internalization of high-affinity, multivalent BCR clusters is apparently promoted by myosin IIa-mediated dynamic contractions in the B cells (Natkanski et al, 2013). There is suggestive evidence in autoimmunity that human GALT may function as a checkpoint for the BCR repertoire by removing autoreactive B cells from the circulation (Vossenkämper et al, 2013). Several other innate immune factors may also contribute to GC formation and function in MALT, such as the cytokines APRIL (a proliferation-inducing ligand) and BAFF/BlyS (B-cell-activating factor of the TNF family/B lymphocyte stimulator).…”
Section: B Cells Are Stimulated In Different Waysmentioning
confidence: 99%